2019
DOI: 10.1186/s12876-019-1098-6
|View full text |Cite
|
Sign up to set email alerts
|

Application value of nomogram and prognostic factors of gastric cancer patients who underwent D2 radical lymphadenectomy

Abstract: BackgroundThe aim of this study was to explore the prognostic factors and establish a nomogram to predict the long-term survival of gastric cancer patients.MethodsThe clinicopathological data of 421 gastric cancer patients, who were treated with radical D2 lymphadenectomy by the same surgical team between January 2009 and March 2017, were collected. The analysis of long-term survival was performed using Cox regression analysis. Based on the multivariate analysis results, a prognostic nomogram was formulated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…More recently, efforts have increasingly focused on developing improved prognostic systems to offer a more accurate prediction of long-term prognosis and risk of recurrence [15,16]. In particular, nomograms have been increasingly adopted within the oncological field for a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, efforts have increasingly focused on developing improved prognostic systems to offer a more accurate prediction of long-term prognosis and risk of recurrence [15,16]. In particular, nomograms have been increasingly adopted within the oncological field for a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…LN metastasis is involved in GC prognostic outcomes [ 2 , 3 ]. Precise preoperative determination of LN involvement in GC is pivotal for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, gastric cancer (GC) is the 5th most prevalent cancer type and the 3rd highest cause of cancer-associated mortalities [ 1 ]. Some studies demonstrated that Lymph node (LN) metastasis is an independent risk index for poor prognosis of GC [ 2 , 3 ]. Precise and exact preoperative identification of LN involvement is important in informing therapeutic decisions for GC patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…LN metastasis is among the primary conditions that in uence the prognosis of GC [2,3]. Precise preoperative determination of LN participation in GC is pivotal for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) constitutes the 5th most frequent cancer and the 3rd top cause of cancer-associated mortality globally [1]. Some studies demonstrated that LN metastasis is an independent risk index for poor prognosis of GC [2,3]. Precise and exact preoperative identi cation of LN involvement is of vital signi cance for treatment strategy decisions in patients with GC [4,5].…”
Section: Introductionmentioning
confidence: 99%